Des difficultés de compréhension du discours spécialisé en L2 par un public non expert. Le cas des étudiants polonophones de FLE face au discours académique - Walicka, Anna (Studia Romanica Posnaniensia, 2017)
The aim of the study reported in this article was to identify the knowledge or skills deficits which make Polish students of foreign languages fail to understand specialised discourse written in their second language (L2). The author analysed the translations proposed by French philology students for a fragment of a French academic text, particularly the translation errors consisting in source text’s meaning transformation (i.e. misinterpretation, incorrect meaning, nonsense). The analysis allows to assume that these errors are the direct result of insufficient knowledge of the L2 in connection with wrong techniques of words’ meaning verification.